2019
DOI: 10.1111/iju.13957
|View full text |Cite
|
Sign up to set email alerts
|

The Urological Association of Asia clinical guideline for urinary stone disease

Abstract: The Urological Association of Asia, consisting of 25 member associations and one affiliated member since its foundation in 1990, has planned to develop Asian guidelines for all urological fields. The field of stone diseases is the third of its guideline projects. Because of the different climates, and social, economic and ethnic environments, the clinical practice for urinary stone diseases widely varies among the Asian countries. The committee members of the Urological Association of Asia on the clinical guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
98
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 298 publications
(543 reference statements)
1
98
0
2
Order By: Relevance
“…Instead, citrate does not have adverse effects if administered in an adequate dose. Oral citrate is a widely recognized prevention against urinary stones in adults in many countries . Oral citrate is also recommended for children in the USA .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, citrate does not have adverse effects if administered in an adequate dose. Oral citrate is a widely recognized prevention against urinary stones in adults in many countries . Oral citrate is also recommended for children in the USA .…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the estimated annual incidence of a first‐episode upper urinary tract stone was 137.9 (191.9 in men and 86.9 in women) per 100 000 . With the increase in the prevalence of urolithiasis, there is a need for an accurate tool by which the risk of a first episode can be predicted to optimize patient screening and treatment strategies . Several studies have identified predictors for the recurrence of a stone after the first episode, the ureteral calculi‐related urosepsis and the stone‐free rate after intervention .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sharing clinical trends and experience among urologists in UAA should hold the potential to improve the level of daily practice. In this respect, the current article, written by Taguchi et al ., could be “a big first step” towards uniting urologists who specialize in urolithiasis among UAA countries …”
mentioning
confidence: 99%